Adaptive Leadership Strategies to Enhance Branch Profitability - Noercahya, Hery; Darusman, Dani Oktafiana; Perdhana, Mirwan Surya (Research Horizon, 2025)
This study explores the impact of leadership strategies employed by Branch Office Heads at BRI Bank on the profitability of their respective work units, with a specific emphasis on branches within the BRI Denpasar Regional Office. Amidst fierce competition in the banking sector, leadership strategies at the branch level are pivotal for meeting profit goals and achieving broader business objectives. Utilizing a qualitative case study approach, data were collected through in-depth interviews and document analysis across various branches in Denpasar. The findings highlight that adaptive leadership, strong team management, and a deep understanding of local market dynamics are critical in sustaining branch profitability. These insights aim to contribute to the advancement of leadership strategies within Indonesia’s banking industry, particularly by enhancing the ability of branch leaders to meet organizational financial objectives effectively.